Microstructure and mechanical property of high strength Mg–Sn–Zn–Al alloys. Issue 9 (13th June 2019) - Li, Yun; Wang, Fang; Hu, Tong; Zheng, Ruixiao; Xiao, Wenlong; Lyu, Shaoyuan; Ma, Chaoli
ABSTRACT: This paper aims to reveal the microstructure and mechanical properties of as-cast and hot-rolled Mg–Sn–Zn–Al based alloys. Three alloys, Mg–5Sn–2Zn (TZ52), Mg–5Sn–2Zn–2Al (TAZ522) and Mg–5Sn–5Al–1Zn–0.2Mn (TAZM5510) alloys were studied. The results revealed that the as-cast alloys showed fine dendritic structures. The TAZM5510 alloys exhibited moderate yield strength of 98 MPa with good elongation of ∼15%, which was comparable to several commercially used Mg die-castings. Mechanical properties were significantly improved after multi-pass rolling. The TZ52 sheet showed a high yield strength of 277 MPa with excellent ductility exceeding 30%, and the TAZM5510 sheet exhibited the highest tensile strength of 386 MPa while keeping desirable elongation of 16.6%. These sheets are termed as strong and ductile Mg–Sn–Zn–Al wrought alloys.